Effects of plug tray cell size on the growth of Atractylodes Chinensis (DC) Koidz seedlings - Shi, Kaixuan; Liang, Juwen; Ji, Fang; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2024)
Atractylodes Chinensis (DC) Koidz is a perennial herb often used as a prescription medicine for influenza, to invigorate the spleen and remove dampness. The quality of the herb is determined by the quality of the seedlings. The traditional A. chinensis seedling production technique has nonuniform seedlings and low mechanisation. The plug seedling technique was used to produce A. Chinensis seedlings. This study was conducted to determine the growth characteristics of A. Chinensis seedlings according to the cell size of plug trays and number of days after sowing. Plant height, stem diameter, rhizome diameter, number of leaves, leaf area, and shoot dry and fresh weight of A. Chinensis seedlings were significantly higher in the P32-D treatment than in the P72, P50, and P32 treatments, but not significantly different from the P28-D treatment 60 d after sowing. The P28-D treatment resulted in a considerable drop in rhizome fresh weight and healthy seedling index, both of which are key indicators for assessing seedling quality. Although the differences in Pn among treatments were not significantly different, Tr was considerably greater in A. Chinensis seedlings treated with P32-D and P28-D than in the other three treatments. The P32-D and P28-D treatments had considerably greater potential maximum photochemical efficiency of PSII, quantum yield of photosystem II, photochemical quenching and electron transport rate than the other three treatments. Root vitality of A. Chinensis seedlings was significantly stronger in the P32-D treatment than in the other four treatments, and it was 1.9 times higher than in the P28-D treatment. The soluble protein, soluble sugar, and starch contents of A. Chinensis seedlings were highest in the P32-D treatment, but the differences among treatments were not significant. LUE, EUE, PY and EY were significantly higher in the P32-D treatment than in the other four treatments, being 1.3, 1.3, 1.4 and 1.4 times higher than in P28-D, respectively. On the other hand, as for the change in the growth of A. Chinensis seedlings according to the number of days after sowing, the growth of shoots and rhizome was most vigorous at the 60 d after sowing, while the fresh weight of the rhizome, which can be considered as an indicator of root growth, increased steadily during the experiment but slowed down after 60 d. As a result, 32-cell deepened plug trays and a seedling nursery for a period of 60-75 d are recommended for commercial cultivation of A. Chinensis seedlings. This will provide technical support for production in A. Chinensis seedling. Key words: Atractylodes Chinensis(DC) Koidz; plug seedling; plug tray cell size DOI: 10.25165/j.ijabe.20241704.8916 Citation: Shi K X, Liang J W, Ji F, He D X. Effects of plug tray cell size on the growth of Atractylodes Chinensis (DC) Koidz seedlings. Int J Agric & Biol Eng, 2024; 17(4): 45–52.